Dynamics of a Blended Lithium-Ion Battery Electrode During Galvanostatic Intermittent Titration Technique. (20th December 2016) - Mao, Z.; Farkhondeh, M.; Pritzker, M.; Fowler, M.; Chen, Z.
Abstract: A multi-particle model is developed and applied to the data from galvanostatic intermittent titration technique (GITT) experiments with varying pulse currents and relaxation periods on a LiNi1/3 Mn1/3 Co1/3 O2 −LiMn2 O4 (NMC-LMO) blended lithium-ion electrode. The good agreement between the simulated and experimental potential-time curves shows that the model is applicable for all GITT conditions considered, but more accurate for the case of small current pulse discharges with long relaxation times. Analysis of the current contribution and the solid-state surface concentration of each active component in the blended electrode shows a dynamic lithiation/delithiation interaction between the two components and between micron and submicron NMC particles during the relaxation periods in the GITT experiments. The interaction is attributed to the difference in the equilibrium potentials of the two components at any given stoichiometry which redistributes the lithium among LMO and NMC particles until a common equilibrium potential is reached.